Reflecting on the process of teaching reflection in higher education. Issue 6 (2nd November 2018) - Bharuthram, Sharita
ABSTRACT: Higher education plays an important role in nurturing life-long learning and critical citizenry. One way to foster these is through developing a reflective practice. Given the importance of reflection, this article discusses the process of teaching reflection in my course, and students' responses to these lessons, with a focus on their understanding of what it means to reflect and on its benefits and challenges. The findings reveal that, while most students are able to adequately articulate what reflection is, they are not able to translate this understanding into practice, and reflection is not viewed as a learning strategy. Students find reflecting on personal issues easier than reflecting on discipline-related ones, and language proficiency could play a role. A reflective practice can be inculcated in students and can lead to the development of criticality; however, the methods used to facilitate this process are crucial. While some of the above findings may be attributed to shortcomings in the course, the article concludes that, for greater effectiveness and for reflection to be viewed as an important practice in developing criticality, as well as a life-long learning practice, the teaching of reflection should be embedded in meaningful and productive ways throughout the curricula.